Cardio-Oncology for the Primary Care Provider - Jhawar Nikita; Mcpherson Alyssa; Chirila Razvan; Ray Jordan (Sciendo, 2023)
Cardiovascular disease is a major cause of mortality among oncologic patients. As cancer therapies continue to evolve and advance, cancer survival rates have been increasing and so has the burden of cardiovascular disease within this population. For this reason, cardio-oncology plays an important role in promoting multidisciplinary care with the primary care provider, oncology, and cardiology. In this review, we discuss the roles of different providers, strategies to monitor patients receiving cardiotoxic therapies, and summarize cancer therapy class-specific toxicities. Continued collaboration among providers and ongoing research related to cardiotoxic cancer therapies will enable patients to receive maximal, evidence-based, comprehensive care.